Investigation of inter-layer bonding property in asphalt pavement based on 3D morphology of reconstructed interface. (24th January 2022) - Ai, Changfa; He, Hongzhi; Zhang, Xinyu; Meng, Huilin; Ren, Dongya
Highlights: Non-destructive separation between layers of the composite specimen was achieved by using silica gel film and spin forming. High precision 3D scanning and reverse modeling technology are used to reconstruct the 3D shape of the interface, and the morphology model based on the interface surface and the volume encapsulation model based on the concave and convex body are constructed. The related indexes based on interface contact feature and interlocking feature are extracted to characterize the inter-layer bonding effect. The RSR model is introduced to evaluate the inter-layer contact and interlocking effects in different structural combinations. Abstract: Specific to the inter-layer bonding property in asphalt pavements considering the reshaping effect of tack coat on the inter-layer interface morphology, non-destructive separation between layers and 3D scanning test were carried out on the pavement structure layers sprinkled with tack coat. At the same time, the reverse modeling technology was used to reconstruct the inter-layer interface morphology and establish the volume encapsulation model based on the concave-convex area on the interface, so as to explore the inter-layer bonding effect in asphalt pavement layers based on the 3D morphology of the reconstructed interface. The results show that: (1) compared with inter-layer area ratio K, inter-layer abundance increment ratio α can more visually characterize the differential contact effect between the upper and lower interfaces, while normalized inter-layer interlocking coefficient IC can clearly reflect the differential characteristics of the interlocking effect between the upper and lower interfaces; (2) rank-sum ratio RSR is introduced in this study to comprehensively evaluate the inter-layer bonding effect, and it is found that the inter-layer bonding effect of the structure combination AC-13/AC-20 is superior to the others, while the structure combination OGFC-13/AC-20 displays the worst inter-layer bonding effect; (3) the inter-layer bonding effect of the densely graded structure is better than that of the open graded structure, and the inter-layer bonding effect of the continuous densely graded structure is better than that of the discontinuous densely graded structure, and the magnitude of the inter-layer shear strength of each composite structure is consistent with the order of its inter-layer contact-interlocking effect.